2006
DOI: 10.1007/s10237-006-0027-0
|View full text |Cite
|
Sign up to set email alerts
|

A Bimodular Theory for Finite Deformations: Comparison of Orthotropic Second-order and Exponential Stress Constitutive Equations for Articular Cartilage

Abstract: Cartilaginous tissues, such as articular cartilage and the annulus fibrosus, exhibit orthotropic behavior with highly asymmetric tensile-compressive responses. Due to this complex behavior, it is difficult to develop accurate stress constitutive equations that are valid for finite deformations. Therefore, we have developed a bimodular theory for finite deformations of elastic materials that allows the mechanical properties of the tissue to differ in tension and compres sion. In this paper, we derive an orthotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…This limitation does not reflect the true nature of native cartilage which has been found to display anisotropic behavior (Wang et al 2003;Ficklin et al 2006). Future work will extend the bimodular stressstrain equation for the collagen constituent to include anisotropic behavior (Klisch 2006a). Also, it has been suggested that to accurately model specific growth experiments a collagen remodeling parameter (related to collagen-specific crosslink or fibril binding molecules) should be included that changes the mechanical properties of the collagen constituent (Klisch et al 2005a).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This limitation does not reflect the true nature of native cartilage which has been found to display anisotropic behavior (Wang et al 2003;Ficklin et al 2006). Future work will extend the bimodular stressstrain equation for the collagen constituent to include anisotropic behavior (Klisch 2006a). Also, it has been suggested that to accurately model specific growth experiments a collagen remodeling parameter (related to collagen-specific crosslink or fibril binding molecules) should be included that changes the mechanical properties of the collagen constituent (Klisch et al 2005a).…”
Section: Discussionmentioning
confidence: 99%
“…Those models were based on a bimodular theory for infinitesimal strains (Curnier et al 1995) in which the material constants may be discontinuous (or jump) across a surface of discontinuity in strain space, provided that stress continuity conditions are satisfied at the surface. Recently, the theory of Curnier et al (1995) was generalized to second-order elasticity by Klisch (2006a). Here, we briefly describe the extension of these theories to the present application.…”
Section: Appendix A: Incremental Growth Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The fibrillar nature of the collagen matrix of cartilage produces a modulus which is significantly higher in tension than compression. The formulation of constitutive models which can describe this behavior has posed a challenge in the cartilage literature; Klisch (2006) presents a novel bimodular theory of elastic materials which extends the analysis to the range of finite deformations. Complementing these analyses of the solid matrix behavior is the successful theory of mixtures which can account for interstitial fluid flow and diffusion of charged ions through the charged collagen-proteoglycan matrix of cartilage, as reviewed by Yao and Gu (2006).…”
mentioning
confidence: 99%